CP-158 Uncritical use of proton pump inhibitors in non-intensive care units of a university hospital. (14th February 2016) - Fritsch, A; Eckstein, B; Brunnert, M; Baehr, M; Langebrake, C; Hilgarth, H
Abstract : Background: Proton pump inhibitors (PPIs) are widely and uncritically used for stress ulcer prophylaxis (SUP) in hospital patients, even though they are not licensed for this indication. Moreover, there is growing evidence that PPIs are not as harmless as they were thought to be. Also, there is an increased risk of pneumonia and Clostridium difficile infections, and recently published studies showed a higher incidence of myocardial infarction 1 and acute kidney injury 2 associated with PPIs. Purpose: The aim of the study was to survey the status quo of the quantity of PPI usage in a university hospital, paying particular attention to plausibility of its use. Material and methods: We scanned the medication of all patients of seven surgical and internal wards in a point prevalence analysis. With the help of the electronic patient record we also screened prehospital medication lists and discharge letters for PPIs. For each newly initiated and continued PPI prescription, plausibility was checked, guided by approved indications and published risk factors 3 4 for gastrointestinal bleeding. Results: The medication of 192 patients was scanned, of whom 66% received a PPI. Of these 56% had a prehospital prescription and this was continued in 89%. At discharge, overall 85% had a PPI listed, with 41% of patients being newly initiated on the treatment. For all patients scanned, we identified 40% of PPI prescriptions being unplausible, and 36% were new inpatient prescriptions. In total, 8% of all patients were leaving hospital with a new unplausible PPI prescription. Conclusion: We found that one-third of PPI prescriptions were not reasonable in our patients. The uncritical prescription of PPIs in hospital may lead to a vicious circle of inpatient prescription, which is continued in outpatient care, without questioning the indication, and further continuation in the case of another hospitalisation. With respect to the growing evidence of the hazard potential of PPIs, it is important to verify the indication for each PPI prescription and reduce unnecessary 'just in case SUP'. References and/or Acknowledgements: Shah, . PLoS ONE 2015 Antoniou, et al . CMAJ Open 2015 García Rodríguez, et al. Circulation 2011 Herzig, et al. J Gen Intern Med 2013 No conflict of interest.